Defective Intestinal Phosphate Absorption in Familial and Non-familial Hypophosphataemia. Issue 5715 (18th July 1970) - Condon, J. R.; Nassim, J. R.; Rutter, A.
Abstract : With an oral phosphate tolerance test a primary defect in intestinal phosphate absorption was found in patients with untreated familial and non-familial hypophosphataemia. It is suggested that this plays a major part in the aetiology of rickets and osteomalacia in these disorders. Vitamin D was shown to have a beneficial effect on intestinal transport of phosphate, though defective absorption was not completely corrected. If intestinal phosphate absorption is normal, oral phosphate supplements will maintain normal plasma phosphate levels even in the presence of a pronounced renal phosphate leak. In familial and non-familial hypophosphataemia the phosphate tolerance test may be a more sensitive index of genetic abnormality than a low plasma phosphate. It may be helpful in distinguishing several syndromes at present classified under non-familial hypophosphataemia, as well as assessing the response to treatment with vitamin D and in investigating intestinal transport of phosphate.